Effects of Dietary Protein and Energy Levels on Growth Performance, Nutrient Digestibility, and Serum Biochemical Parameters of Growing Male Mink (Neovison vison) - Han, Feifei; Wang, Jing; Chen, Lihong; Zhong, Wei (Frontiers in Veterinary Science, 2022)
The objective of this experiment was to determine the optimum dietary metabolic energy (ME) and crud protein (CP) levels of growing male mink. One hundred forty-four healthy male mink at 75d were randomly allocated into six groups with 24 replicates, which was one mink for each replicate. The mink were fed six experimental diets with two CP levels (31.59% and 35.63%) and three ME levels (14.17,15.96 and 17.73 MJ/kg) for a 7d preliminary period and then for 88d experimental period. The final body weight (BW), average daily gain (ADG), feed conversion ratio (FCR) and fat digestibility, energy intake, the concentration of glucose (GLU) and low-density lipoprotein (LDL) of the mink were significantly increased by the CP or ME levels (P < 0.05). In addition, CP levels significantly (P < 0.01) increased the N intake and N retention. Dietary ME levels increased the utilization of gross energy. Obviously, there were significant CP × ME interaction for the final BW, ADG, fat digestibility, energy utilization, and GLU, LDL (P < 0.01) and triglyceride contents (P < 0.05). Therefore, the optimum CP and ME levels were 35.97% and 18.18 MJ/kg, which can improve growth; enhance nutrient digestion; and promote blood lipid metabolism in growing mink.